A comprehensive review on advances and applications of industrial heat pumps based on the practices in China. (15th September 2016) - Zhang, Jing; Zhang, Hong-Hu; He, Ya-Ling; Tao, Wen-Quan
Highlights: Comprehensively reviewing industrial heat pump systems in China for the first time. Research and application advances in industrial heat pumps in China are discussed. Three typical examples of using industrial heat pumps are discussed in details. It identifies the further research needs on industrial heat pump in China. Abstract: An industrial heat pump can upgrade heat from a low temperature level to a high temperature level with the aid of an external energy source. It has received considerable attention as an efficient means of waste energy recovery in the recent years in China. This paper summarizes the research work done and advances in the application of industrial heat pump systems in China, including advances in refrigerants, multistage system, double-effect absorption system, compression–absorption system, solar assisted system, and chemical heat pump system. Industrial heat pumps used in three industrial fields (drying of wastewater sludge, crude oil heating in oil field, and process heating in printing and dyeing) are discussed in detail. Three basic problems in designing an engineering heat pump system, i.e., selection of the type of heat pump and determination of its capacity, energetic and exergetic analyses of the heat pump, and estimation of investment payback time are discussed in the above three industries, respectively. Further research needs in China on industrial heat pumps are proposed, which may also be beneficial to the international community.